2010
DOI: 10.1007/s11259-010-9351-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the protective effect of bovine lactoferrin against lipopolysaccharides in a bovine mammary epithelial cell line

Abstract: Lactoferrin (Lf) is a non-haem iron-binding glycoprotein with a molecular weight of about 80 kDa, synthesized by glandular epithelial cells and stored in the secondary granules of neutrophils. The physiological significance of Lf is related to non-specific immune defence against pathogens, immunomodulatory activity, iron homeostasis, antioxidant properties and regulation of cell growth. Lf is a bioactive component of the mammary secretions and its modulatory and defensive functions do affect the newborn and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 48 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…However, their transformation may alter their behaviour. For example, it has been reported that the bovine cell lines MAC-T cells are deficient in LAP and inducible nitric oxide synthase (iNOS) expression (29) and the BME-UV1 cell line may lack some functional lipopolysaccharide (LPS)-responsive elements (30). This is why ideally studies based on one or several cell lines should also involve primary cells derived from several animals.…”
Section: Strengths and Weaknesses Of Experimental Protocols Used To I...mentioning
confidence: 99%
“…However, their transformation may alter their behaviour. For example, it has been reported that the bovine cell lines MAC-T cells are deficient in LAP and inducible nitric oxide synthase (iNOS) expression (29) and the BME-UV1 cell line may lack some functional lipopolysaccharide (LPS)-responsive elements (30). This is why ideally studies based on one or several cell lines should also involve primary cells derived from several animals.…”
Section: Strengths and Weaknesses Of Experimental Protocols Used To I...mentioning
confidence: 99%
“…Lactoferrin, due to its cationic nature, shows high affinity for anionic molecules and is capable of binding LPS, allowing for direct neutralization and limiting activation of macrophage CD14 and other pattern recognition receptors (Legrand et al, 2005) important for initiation of innate immune responses. The LPS-binding abilities of lactoferrin have been reported in various in vitro and animal models using both bovine (Dohler et al, 2002;Pecorini et al, 2010) and human lactoferrin (Zhang et al, 1999;Baveye et al, 2000;Li et al, 2012). In this context, the ability of lactoferrin to prevent LPS-induced inflammatory responses may also play a key role in preventing chronic inflammation mediated by bacterial translocation from the gut, as has been described in obesity (Frazier et al, 2011).…”
Section: Immune-modulationmentioning
confidence: 99%
“…Under in vitro conditions, the neutralizing activity of Lf has also been evidenced. It provided a protective effect against LPS-induced cytotoxic damage to cells from the mucosal covering of epithelial cells, which were from bovine mammary glands [57] and colon [58].…”
Section: Neutralizing Effects Of Lf On the Lps-induced Inflammatory Rmentioning
confidence: 99%